Econometric modelling of time series applied in the generation of subsidies in the milk production chain in Rio Grande do Sul - Souza, Francisca Mendonça; de Paula, Brunna Aver; Baggio, Daniel Knebel; Brum, Argemiro Luis; Sausen, Juliana da Fonseca Capssa Lima (Ciência e Natura, 2021)
The purpose of this article is to make short-term forecasting using the methodology Box & Jenkins, the Johansen method and the Granger causality, and the impulse-response function between variables price and milk production in Rio Grande do Sul’s market. The monthly price series of milk and its production in Rio Grande do Sul were analysed, in the period from January 1995 to December 2017. The model that suits best, for forecasts, the data of the series of the milk price paid to the producer was an ARIMA (1, 1, 1) and production was SARIMA (1, 1, 1) (1, 1, 1)6, which provided reasonable estimates of forecasts for the months from February to July of 2017. The use of Johansen methodologies identifies the existence of the one cointegration vector and a long-term equilibrium relation between variables price and production of the milk. When we analyse Granger’s causality, the results point to a two-way relationship, that is, prices influence milk production and vice versa. The analysis of the impulse-response function showed that the shocks present significant impacts between production and cost, both in terms of duration and intensity.